T cell help controls the speed of the cell cycle in germinal center B cells - Gitlin, Alexander D. (Science, 2015)
The germinal center (GC) is a microanatomical compartment wherein high affinity antibody-producing B cells are selectively expanded. B cells proliferate and mutate their antibody genes in the dark zone (DZ) of the GC, and are then selected by T cells in the light zone (LZ) on the basis of affinity. Here we show that T cell help regulates the speed of cell cycle phase transitions and DNA replication of GC B cells. Genome sequencing and single-molecule analyses revealed that T cell help shortens S phase by regulating replication fork progression while preserving the relative order of replication origin activation. Thus, high affinity GC B cells are selected by a mechanism that involves prolonged dwell time in the DZ where selected cells undergo accelerated cell cycles.